Polioencephalomalacia (PEM)-Current research status - D.A. Sapienza; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1975)
In ruminants fed high grain rations, a condition called polioencephalomalacia (PEM), characterized by central nervous system derangement, can develop. It usually is noninfectious, responds to thiamin injections, and is characterized by sudden onset. Using artificial rumen techniques, we established that PEM results from a bacteria-produced enzyme in the rumen that converts the vitamin thiamin to a nonusable alternate form, pyrithiamin, which in turn caused severe metabolic disturbances in the central nervous system.
Keywords: Cattlemen' s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Polioencephalomalacia; Thiamin